A CASE REPORT ON WELL KNOWN BUT HAS TO BE REPORTED ADVERSE EFFECT OF PHENYTOIN-INDUCED RASH AND ASSESSMENT OF ITS SEVERITY BASED ON ADVERSE DRUG REACTION REPORTING SCALES - KAUR, AMANJOT; SINGH, JASNINDER (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Phenytoin is an aromatic antiepileptic drug, commonly used for the purpose of treating generalized tonic clonic and partial seizures. The drug has been known to cause hypersensitivity reaction, which can be life-threatening by involving internal organs, and is referred as anticonvulsant hypersensitivity syndrome. The treatment in such cases is the immediate discontinuation of the agent causing the reaction and replacing the treatment with other non-aromatic anticonvulsant agent. This case report presents an adverse drug reaction and occurs within 1 week of starting the treatment, a well-known but has to report this adverse effect.